An integrated and automated calibration system for pneumatic piston gauges. (February 2019) - Yang, Yuanchao; Driver, R. Gregory; Quintavalle, John S.; Scherschligt, Julia; Schlatter, Katie; Ricker, Jacob E.; Strouse, Gregory F.; Olson, Douglas A.; Hendricks, Jay H.
Highlights: An automated calibration system for pneumatic piston gauges. Factors affecting the transducer-aided crossfloat (TAC) method. The transducer line volume should be minimized. A pressure difference up to 3% does not affect the calibration results. An integrated system with two pressure transducers covering the low and high ranges. Abstract: Recently, a transducer-aided crossfloat (TAC) method for pneumatic piston gauges was proposed. The concept is to use a pressure transducer as a very short-term transfer standard between the standard piston gauge and the test one. Different from the traditional method, a near-perfect balance condition is no longer required and the trim mass adjustment can be avoided. Here we present the detailed studies of the TAC method including the effects of the dead volume of the transducer line, the deviation from the balance condition, and the transducer resolution parameter. Based on the TAC method, an integrated and automated calibration system was designed and developed, which incorporates the manifold and the software. Two high-resolution pressure transducers with the range of 1.4–14 MPa are used to cover the wide calibration range from 10 kPa to 7 MPa. The automated system has the functions of pressure and piston position control, valve operation, and data acquisition.